Theoretical study of the dose measurements reliability with longitudinally arranged dosimetry films in materials with different densities; Journal of Instrumentation; Vol. 15 : Radiation from Relativistic Electrons in Periodic Structures (RREPS-19) - Bulavskaya A. A. Angelina Aleksandrovna; Cherepennikov Yu. M. Yuriy Mihaylovich; Grigorieva (Grigorjeva) A. A. Anna Anatoljevna; Miloichikova I. A. Irina Alekseevna; Startseva Zh. A. Zhanna Aleksandrovna; Stuchebrov S. G. Sergey Gennadevich; Velikaya V. V. Viktoriya Valerjevna (2020, 2020)
Title screen